IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT DESA KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS - Hera Fahdilah Vio; Alizar Isna; Slamet Rosyadi (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Poverty alleviation efforts continue to be carried out both at the central and regional levels. The community is expected to have independence in solving the economic problems faced. Problems in each region vary as well as at the village level. Independence in facing existing poverty problems is called empowerment. So that people are able to have fighting power to solve economic problems. Central and local governments need to provide opportunities for the community to increase capacity. With various empowerment programs carried out both for the community and for the apparatus, it is expected to be able to increase their respective capacities. This research was conducted in several villages in Kedungbanteng District to determine the driving and inhibiting factors for the implementation of empowerment programs. The research was conducted with a qualitative approach. The supporting factor for the smooth running of the empowerment program is the spirit of patriotism possessed by the actors and assistance from the Village Community Empowerment Social Office. Meanwhile, the inhibiting factors for the implementation of empowerment programs are poor human resources and dependence on funding from the government.